2022
DOI: 10.3390/microorganisms10112250
|View full text |Cite
|
Sign up to set email alerts
|

Fungicolous Fungi on Pseudosclerotial Plates and Apothecia of Hymenoscyphus fraxineus and Their Biocontrol Potential

Abstract: In the present work, research tasks were carried out in the search for fungi with potential biocontrol possibilities in relation to the ash dieback pathogen, Hymenoscyphus fraxineus. In the years 2012–2021, dead petioles of F. excelsior and F. mandshurica were collected, on which morphological structures of H. fraxineus showed unusual symptoms of dying (apothecia) and signs of colonization by other fungi (pseudosclerotial plates). Based on morphological and molecular phylogenetic data, 18 fungal taxa were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Until now, biological protection measures have primarily focused on the identification and testing of various antagonistic microorganisms, primarily endophytic or saprophytic fungi in the tissues of ash trees ( Fraxinus spp. ), and their potential against H. fraxineus (Bakys et al., 2022; Becker et al., 2020; Bilański & Kowalski, 2022; Haňačková, Havrdová, et al., 2017; Kowalski & Bilański, 2021, 2022; Nawrot‐Chorabik et al., 2021; Schlegel et al., 2016). An antagonism study in planta showed that the practical application of endophytic fungi reduced necrotic lesions on trees (Barta et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, biological protection measures have primarily focused on the identification and testing of various antagonistic microorganisms, primarily endophytic or saprophytic fungi in the tissues of ash trees ( Fraxinus spp. ), and their potential against H. fraxineus (Bakys et al., 2022; Becker et al., 2020; Bilański & Kowalski, 2022; Haňačková, Havrdová, et al., 2017; Kowalski & Bilański, 2021, 2022; Nawrot‐Chorabik et al., 2021; Schlegel et al., 2016). An antagonism study in planta showed that the practical application of endophytic fungi reduced necrotic lesions on trees (Barta et al., 2022).…”
Section: Introductionmentioning
confidence: 99%